Faktor-Faktor Penyebab Terpilihnya Anggota Legislatif dari Partai Gerindra di Kabupaten Aceh Tamiang Pada Tahun 2019 - M. Luthfi Hidayat; R Hamdani Harahap; Amir Purba (PERSPEKTIF, 2022)
Aceh Tamiang Regency is one of the regencies through the division in 2002 in Aceh Province. In the 2019 Legislative Election, the Gerindra Party of Aceh Tamiang Regency succeeded in defeating the Party that has always been the winning party in the previous period, namely the Aceh Party, a party with religious ideology or conservative Islam . The majority vote was won by the Great Indonesia Movement Party by getting 6 seats or 20% of the total seats in the Aceh Tamiang DPRK. This research was conducted with in-depth interviews with 5 (five) informants and Focus Group Discussions (DKT) with 5 (five) people, the informants answered about what factors led to the election of legislative members in Aceh Tamiang Regency in 2020. Many people assumes that money and the popularity of the main capital in winning the Pileg contestation. However, in the context of the 2019 Aceh Tamiang Pilleg, this was not entirely the case, many other factors led to the election of legislative members from the Gerindra Party. Because many candidates who have more financial capital but are not elected, the electability of legislative members is influenced by their good track record, massive performance of the success team, and the support of religious and community leaders